Examination of Pervasiveness of Elevated Serum Uric Acid Level and Microalbuminuria in Prehypertension (Academia Journal of Medicine, 2020)
Background: The relationship between uric acid and microalbuminuria in healthy adults without other cardiovascular risk factors may help to clarify the role of uric acid in cardiovascular disease. In this study, we examined that elevated serum uric acid level was associated with microalbuminuria. Subjects and Methods: Study was done on both male and female prehypertensive patients of age more than 18 years and less than 60, admitted in wards and attending OPD. Controls were normotensive patients admitted in wards who were matched for age, sex and confounding factors. Results: Hyperuricemia was found in 53 (15.14%) patients with prehypertension compared to 32 (9.14%) patients with normal BP. Thus hyperuricemia was seen in patients of prehypertension which was highly significant as P
Keywords: Serum Uric Acid; Microalbuminuria,; Prehypertension